Nickel and Zinc Tolerance and Co-Tolerance in Populations of Deschampsia cespitosa (L.) Beauv. Subject to Artificial Selection - Beatrix A. K. von Frenckell-Insam; Hutchinson, Thomas C. (The New phytologist, 1993)
The occurrence of co-tolerance to four heavy metals was investigated among seedlings selected from three different non-tolerant Canadian and German Deschampsia cespitosa (L.) Beauv. populations. Plants selected following screening of seedlings in solution containing Ni or Zn ions, subsequently showed enhanced tolerance to Ni and Zn, respectively. `Nickel screened' seedlings exhibited no increased tolerance to Zn. `Zinc screened' seedlings, in contrast, had somewhat elevated tolerance to Ni in two of the three populations tested (Elm and Cypress Lake). Thus, co-tolerance may be a population-specific rather than a species-specific response. Individual Elm plants screened for Ni response did not have elevated Zn tolerance, whereas `Zn screened' seedlings did show elevated Ni tolerance. This confirms the result from the population tolerance tests. We conclude that co-tolerance is not a reciprocal process. While the selection for one metal may confer elevated tolerance to a second, selection for the second may not confer tolerance to the first.